Diagnosis and remediation of mathemaphobia among junior secondary students in Etche Local Government Area of Rivers State - Nwuke, Ndubuisi; Anaekwe, Eugenia (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2023)
The study conducted an educational intervention to enhance the academic outcomes of junior secondary students with mathemaphobia in Etche Local Government Area of Rivers State by focusing on the diagnosis and remediation of their mathematical challenges. This research employed a quasi-experimental design, involving 100 Junior Secondary School two (2) students with mathemaphobia in Algebra. The study involved the random selection of two junior secondary schools, with one serving as the experimental group and the other as the control group. Three steps were included in the identification and selection of mathemaphobic students for participation in the study. viz: the existing school records and teachers' evaluations, and the Diagnosis of Mathemaphobia Questionnaire (DMQ). While to assess the students' performance in Algebra, the Algebra Achievement Test (AAT) was employed. Experts in mathematics education validated the research instruments. Cronbach Alpha and Kuder-Richardson (KR-21) formulas were used to determine their reliability to obtain indices of 0.89 and 0.92 for DMQ and AAT respectively. The control group was instructed using lectures, while the experimental group used Polya's problem-solving strategy to teach Algebra to the students. The mean, Standard Deviation, and ANCOVA were used for data analysis. The results showed that students with mathemaphobia taught using Polya's problem-solving strategy performed better than their counterparts taught using the lecture method in terms of achievement and retention of concepts of Algebra. The study recommends that mathematics teachers incorporate Polya’s problem-solving model in their teaching methods, encouraging all students to actively participate and collaborate to enhance their learning outcomes.